2019
DOI: 10.5398/tasj.2019.42.1.13
|View full text |Cite
|
Sign up to set email alerts
|

Cryopreservation of Swamp Buffalo Semen in Skim Milk Yolk-based Diluent with Two Different Cryoprotectants

Abstract: The successful of artificial insemination (AI) in buffalo is still low. The quality of frozen semen determines the successful of AI program. Glycerol is widely used for cryopreservation of buffalo semen with unsatisfactory results due to its toxicity and antifertility properties. This study aimed to investigate the effect of glycerol and dimethylformamide (DMF) concentrations in skim milk egg yolk (SMEY)-based diluent on the quality of frozen-thawed swamp buffalo bull semen. Fresh semen was divided into eight … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 7 publications
1
9
2
Order By: Relevance
“…The viability of buffalo sperm in this study (35.33 -66.67%) was different from reports Herbowo et al (2019) which used tris egg-yolk diluent (49.08-61.52%) and reports Ansari et al (2017) which used andromed® and tris egg-yolk diluents (61.5-67.5%). The difference in viability was caused by different types of buffalo, type of diluent and feed (Manjunath, 2012).…”
Section: The Frozen Semen Qualitycontrasting
confidence: 91%
See 2 more Smart Citations
“…The viability of buffalo sperm in this study (35.33 -66.67%) was different from reports Herbowo et al (2019) which used tris egg-yolk diluent (49.08-61.52%) and reports Ansari et al (2017) which used andromed® and tris egg-yolk diluents (61.5-67.5%). The difference in viability was caused by different types of buffalo, type of diluent and feed (Manjunath, 2012).…”
Section: The Frozen Semen Qualitycontrasting
confidence: 91%
“…However, the abnormality value in this study was almost the same as the abnormality of buffalo sperm in tris-egg yolk diluent at different glycerol concentrations (7.80-16.30%) (El-Sisy et al, 2016). The percentage of PMI of buffalo sperm in this study was higher than PMI of buffalo sperm in Pakistan (44.4-46.8%) that used andromed® and tris egg-yolk diluent (Ansari et al, 2017) but not different from PMI of buffalo sperm in Ciawi that used tris egg-yolk diluent (51.38-62.41%) (Herbowo et al, 2019).…”
Section: The Frozen Semen Qualitycontrasting
confidence: 52%
See 1 more Smart Citation
“…Before the freezing process, the semen should be equilibrated to adapt the sperm to the freezing conditions. Equilibration of sperm has been carried out with various times and temperatures, for example, with temperatures of 4 o C for 6 hours (Herbowo et al, 2019) and 5 o C for 22 hours (Dwinofanto et al, 2018). The metabo-lism of sperm can be suppressed if the semen is cooled at 0 o C-5 o C. Stress conditions of sperm can interfere with the process of inhibition of phosphorylation and phospholipid oxidation, which results in the increased production of reactive oxygen species (ROS) in the semen, and excessive levels of ROS in the cells can increase the oxidation of lipids, proteins, and DNA.…”
Section: Discussionmentioning
confidence: 99%
“…This demonstrated that the addition of Noni fruit extract in egg yolk citrate diluent might significantly preserve the standards of thin tail ram sperm during storage at 5°C for 6 days, even though the best results were obtained at D-5. The result also showed that the infused of noni extract in P1 (4%) and P2(6%) to the sperm diluent could maintain the sperm post thawing motility (PTM) in 40% which still suitable for insemination [11]. The high percentage of sperm motility in P1 and P2 due to the high vitamin C content of noni fruit [12] which was 29.29 mg/ml [13].…”
Section: Resultsmentioning
confidence: 99%